O ator antes da cena: procedimentos de criação através da linha de ações físicas em Stanislavski e Grotowski - Jo?o Paulo Valadares Coimbra (2012)
This paper aims to revisit, on the prism of "physical action" some processes of creation of Konstantin Stanislavski and Jerzy Grotowski name a few co-related concepts such as "if" magic, "given circumstances", "task", "super-task", speaks scenic and "time-rhythmic" in Stanislavski and "discipline and spontaneity, "Impulses", "associations", "contact" and "total action" in Grotowski. The idea is to search a text that offers an easy to read, for both professionals and students of theater, in order to contribute to the solution of practical problems present in the daily lives of actors and directors who use or would like to use physical action in their work.